Práticas pedagógicas e relações étnico-raciais: uma análise da construção da identidade negra da criança nos anos iniciais do ensino fundamental de uma escola pública da cidade de João Pessoa - Medeiros, Maria Fabrícia de (2019)
This research investigates the Pedagogical Practices and Ethnic-Racial Relations and analyzes the construction of the black identity of the child in the early years of elementary school of a public school in the city of João Pessoa. Its main objective is to analyze the pedagogical practices of teachers focused on ethnic-racial relations and their possible influences on the construction of black identity of children in the first years of elementary school in a public school in João Pessoa - PB. The research subjects were two teachers, children aged between 6 and 8, in the first two years of school, being: 22 (10 girls and 12 boys) in a room and 21 (12 girls and 09 boys) in another; In both classes there were black and white children. The research was qualitative, ethnographic, the data collection instruments were questionnaires applied with the teachers, participating observations, video recording, field diary, photographs and informal conversations with the children, the data analysis was based on the Content Analysis, techniques of microgenetic analysis. It was assumed that the construction of the black identity of the children is strongly and directly influenced by the pedagogical practice of the teachers, since the professional being is not separated from the personal being, thus encompassing their own life-acquired learning. Identity is / is part of your daily actions within the school. The child, who is in the process of building his or her identity and directly depends on the first and intense social interactions that happen basically in the family and school, and knowing that they observe and imitate adults, may consequently deny, affirm and / or redefine their black identity already started and directed in the family environment in this daily contact with their teachers. Thus, it is evident that the research results indicated that the initial and continuing education of teachers regarding the subject in question is still an inefficient training and that privileges the quantitative results, unable to prepare their professionals to deal with the issues. Diversities and with complex and necessary themes the real social demands. Thus, it is appropriate to say that I found committed teachers and that their practices related to the theme proposed in this thesis are much more supported in their lifelong constructions. It was noticed that the children, still so young, mostly carried very remarkable social representations about the color representation and physical characteristics of black people that was not shown until provoked / confronted during the interactive workshops. The construction of the identity of black children has been elaborated even before entering school, based on their family and social experiences, and that they have a strong influence on the formation of an identity that is denied and not recognized. Later, especially through the teachers' pedagogical practices, the children moved from denial to self-affirmation, resignifying their identities.